2007
DOI: 10.1590/s0037-86822007000300009
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome cardiopulmonar por hantavírus no Triângulo Mineiro e Alto Paranaíba, Minas Gerais, 1998-2005: aspectos clínico-epidemiológicos de 23 casos

Abstract: RESUMO Foram analisados os achados epidemiológicos, clínicos, laboratoriais e terapêuticos de 23 casos de síndrome cardiopulmonar por hantavírus, identificados sorologicamente ou por imunohistoquímica em hospitais do município de Uberlândia, Minas Gerais. Febre (100%), dispnéia (100%) e mialgias (78%) foram os sintomas mais frequentemente observados nesta casuística. Os sinais físicos mais prevalentes foram hipotensão (65%) e taquicardia (65%). Achados laboratoriais mais comuns incluíram trombocitopenia (96%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 22 publications
1
6
0
4
Order By: Relevance
“…However, none of the antibody-positive individuals reported any symptoms suggestive of HPS (Jonsson et al 2010), indicating that the infections were mild or asymptomatic, as previously reported in Colombia and Brazil (Limongi et al 2007, Londoño et al 2011.…”
Section: Discussionsupporting
confidence: 65%
“…However, none of the antibody-positive individuals reported any symptoms suggestive of HPS (Jonsson et al 2010), indicating that the infections were mild or asymptomatic, as previously reported in Colombia and Brazil (Limongi et al 2007, Londoño et al 2011.…”
Section: Discussionsupporting
confidence: 65%
“…In this region, HPCS is caused by ARAV, which has been cited by Figueiredo et al 2 as probably the most virulent hantavirus in the Americas. It is possible that in many of our patients, HPCS was only suspected when they became severely ill, and this negatively affected their survival 2,38 . However, delays in treating HPCS have also been found to occur in other Brazilian regions, with HPCS case fatality rates caused by other hantaviruses that ranged from 44% in the state of Mato Grosso to 26% in the state of Santa Catarina 18,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Esta observação mostra a restrição hídrica como uma importante medida terapêutica no tratamento dos pacientes com SPCVH, uma síndrome de extravasamento capilar em que os grandes volumes infundidos terminam no interstício pulmonar agravando a insuficiência respiratória 1 Entretanto, alguns autores recomendam a infusão hídrica visando a aumentar o débito cardíaco e a perfusão tecidual. Porém, num estudo com 23 pacientes, realizado, na região do triângulo mineiro, os autores não encontraram relação entre sobrevida e infusão hídrica 16 .…”
Section: Figuraunclassified